(untitled) (Research, Society and Development, 2024)
In Veterinary Medicine, fibrous osteodystrophy, also known as “rubber jaw”, is the main lesion caused by secondary hyperparathyroidism. This disease is not considered common and tends to mainly affect young animals, in the growth phase, or those with advanced chronic kidney disease. To confirm this disease, physical and complementary tests are necessary, such as indicators of kidney function and imaging tests. Treatment depends on the stage of kidney disease, which will directly influence the patient’s survival time. In view of the above, the present work aims to report a case of fibrous osteodystrophy due to secondary renal hyperparathyroidism in an adult Shih Tzu dog.